2018
DOI: 10.1080/23752696.2018.1499419
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: a case study of a partnership approach to skills development through student engagement in Bristol’s Green Capital year

Abstract: HEIs are well placed to engage with local communities, and can connect students with organisations through several pathways, such as volunteering opportunities, placements, internships, or projects. The University of the West of England, Bristol (UWE), the University of Bristol and their respective Students' Unions have been working in partnership with the city and local communities, using HEFCE Catalyst funding to promote student involvement in sustainability activity during Bristol's year as European Green C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Scholars propose that sustainability learning in higher education should focus on learning content, pedagogy and the learning environment (Greig & Prindle, 2019). Some of the preferred procedures for developing students' competencies in sustainability are placements, internships and authentic 'real-world' projects (Bigg et al, 2018). Instructors in higher education could use assessment tasks that are problem-based (i.e., scenario analysis, forecasting, back-casting and case studies) and that generally encourage students to think about alternative futures and evaluate the consequences of different decisions and actions.…”
Section: Discussion and Implications For Teaching And Learning Practicesmentioning
confidence: 99%
“…Scholars propose that sustainability learning in higher education should focus on learning content, pedagogy and the learning environment (Greig & Prindle, 2019). Some of the preferred procedures for developing students' competencies in sustainability are placements, internships and authentic 'real-world' projects (Bigg et al, 2018). Instructors in higher education could use assessment tasks that are problem-based (i.e., scenario analysis, forecasting, back-casting and case studies) and that generally encourage students to think about alternative futures and evaluate the consequences of different decisions and actions.…”
Section: Discussion and Implications For Teaching And Learning Practicesmentioning
confidence: 99%
“…Carlisle, Gourd, Rajkhan, and Nitta (2017) reported that community-based learning enhances participation and volunteerism, and improves students' ability to work with others and openness to new ideas. Bigg et al (2018) found that student collaboration across two universities in a large-scale community-based project reinforced students' academic learning through its engaged approach, and also fostered a sense of shared community between students. Reflection has been found to be key in integrating the triad of interdisciplinary teaching, experiential learning, and community engagement (Culhane, Niewolny, Clark, & Misyak, 2018).…”
Section: Literaturementioning
confidence: 99%
“…With some exceptions (e.g. Bigg et al, 2018), most empirical literature on student engagement focuses on a single aspect of an assignment. Missing is a holistic study of student engagement in a multifaceted, interdisciplinary learning context that incorporates many different best practices that existing studies have identified as ideal for engaging students.…”
Section: Literaturementioning
confidence: 99%
“…Carlisle et al (2017) reported that community-based learning improves students' ability to work with others and openness to new ideas. In mathematics education, collaborative learning's popularity surged in the 1980s, but it has since continued to evolve (Bigg et al, 2018) found that student collaboration across two universities in a large-scale community-based project reinforced students' academic learning through its engaged approach, and also fostered a sense of shared community between students.…”
Section: Collaborative Learningmentioning
confidence: 99%